Metabolomic and lipidomic changes in heat-stressed chickpea seeds - Jha, Uday Chand; Warburton, Marilyn L.; Nayyar, Harsh; Siddique, Kadambot H. M.; Prasad, P. V. Vara (Frontiers in Plant Science, 2025)
Extreme climate induced heat stress during the reproductive phase significantly reduces yield and seed quality in chickpea, a vital cool-season pulse crop. While chickpea plants deploy various biochemical and molecular mechanisms, including the production of protective compounds and heat shock proteins to cope with heat stress, the metabolomic and lipidomic bases of heat tolerance remain poorly understood. This study used untargeted metabolomics and lipidomics to identify key metabolites, lipids, and potential biomarkers in seeds of a heat-tolerant (PI518255) and a heat-sensitive (PI598080) chickpea genotypes exposed to heat stress (35 °C day/20 °C night) under controlled environments. Results from volcano plot analysis revealed that 65 metabolites and 131 lipids were upregulated, while 17 metabolites and 195 lipids were downregulated under heat stress. Heatmap analysis showed that the heat-tolerant genotype had elevated metabolites (Naringenin, Astilbin,1-O-Cinnamoyl-(6-arabinosylglucose), Hesperetin 7-glucoside, luteolin, and neoandrographolide) and lipids [dimethylphosphatidylethanolamine (dMePE), phosphatidylinositol phosphates (PIP), phosphatidylethanolamine (PE), phosphatidylcholines (PC), phosphatidylglycerol (PG), phosphatidylinositol (PI), diacylglycerol monogalactoside (DGMG) (36:5), monogalactosyldiacylglycerol (MGDG), phosphatidic acid (PA), phosphatidylmonomethylethanolamine (PMe), Biotinyl Phosphatidylethanolamine (BiotinylPE), (O-acyl)-omega-hydroxy fatty acids (OAHFAs)], which may serve as diagnostic biomarkers for heat tolerance. Pathway enrichment analysis (KEGG) identified several heat stress-responsive metabolic pathways, including the pentose phosphate pathway, pyruvate metabolism, citrate (TCA) cycle, glyoxylate and dicarboxylate metabolism, starch and sucrose metabolism, glycolysis/gluconeogenesis, and cysteine and methionine metabolism. Lipid metabolic pathways involving MGDG, glycerophosphocholine, PI, PA, PC, phosphatidylcholines, lysophosphatidylcholine (LPC), lysophosphatidylglycerol (LPG), glycerophosphoinositol, and phosphoglyceric acid were also significantly affected. Future research employing targeted metabolomics and lipidomics profiling could elucidate candidate markers to enhance seed yield and quality, and support breeding programs to develop heat- and climate- resilient chickpea cultivars.